Dimensões do corredor bucal e sua relação com a distância inter pré-molar e intercomissural - Mello, Patrícia Bicalho de [UNESP]; Gandini Júnior, Luiz Gonzaga [UNESP]; Gandini, Márcia Regina Elisa Aparecida Schiavon [UNESP]; Pinto, Ary Dos Santos [UNESP] (My University, 2014)
The objective of the study was to analyze the size of buccal corridor during the smile of individuals from 10 to 19 years of age and to determine whether there is a relationship among buccal corridor, inter premolar distance, inter commissure width. Standard digital frontal photographs in posed broad smiles and dental casts were taken of a sample of 150 individuals divided into 5 age groups of 30 individuals: 10-11 years old (G1), 12-13 years old (G2), 14-15 years old (G3), 16-17 years old (G4), 18-19 years old (G5). Distances among the cusps of superior first premolars and buccal corridors were measured for subsequent comparisons using the Image Tool 3.0 program. Data was analyzed using Anova. The SNK test and Tamhane test were applied. The mean values of the buccal corridor ranged from 4.00-to 10.69 mm on the right side and from 4.06 to 11.43 mm on the left side. In percentage related with intercomissure width each side of the buccal corridor ranged from 7.46 to 16.47% on the right side and from 7.58% to 17.61% on the left side. Buccal corridors were different between genders and increased with age. Males have bigger buccal corridors than females, but there is no difference between gender when calculated as a percentage related with the inter commissure width. The inter premolar width is significantly correlated with inter commissure widths of female individuals 14-15 years old and 18-19 years old, and with the right linear buccal corridor of males and females aged 14-15 years old.

O objetivo desse estudo foi analisar o tamanho do corredor bucal durante o sorriso de indivíduos, de dez a 19 anos de idade, e determinar se há uma relação entre o corredor bucal, a distância inter pré-molar e a largura intercomissural. Fotografias padronizadas digitais frontais de sorriso posado e modelos de gesso foram realizados em uma amostra de 150 indivíduos divididos em cinco grupos de 30 indivíduos: 10-11 anos (G1), 12-13 anos (G2), 14-15 anos (G3), 16-17 anos (G4), 18-19 anos (G5). As distâncias entre as cúspides dos primeiros pré-molares superiores e o corredor bucal foram medidas para subsequente comparação, utilizando o software Image Tool. Os dados foram analisados utilizando Anova, e os testes SNK e Tamhane foram aplicados. Os valores médios do corredor bucal variam de 4,00 a 10,69 mm do lado direito, e de 4,06 a 11,43 mm do lado esquerdo. Em percentagem variou de 7,46 a 16,47% do lado direito, e de 7,58% a 17,61% do lado esquerdo. O corredor bucal foi diferente entre os gêneros e aumentou com a idade. Não houve diferença entre os gêneros, quando calculado em percentagem. A distância inter pré-molar está correlacionada com a largura intercomissural no gênero feminino de 14-15 anos e 18-19 anos, e com o corredor bucal linear em ambos os gêneros de 14-15 anos.
Dimensions of buccal corridor and relationship, with inter premolar distance and inter commissure width
Keywords: Esthetics; Smiling; Sentition; Estética; Sorriso; Dentição